A tumour of vascular origin in a horse. (26th November 2020) - Wise, J. C.; Crosby, D. E.; Walton, A. N.; Neef, A.; Shearer, P. L.; Woodward, D. J.; Hilbert, B. J.
Summary: Tumours of vascular origin are uncommon in horses. This report describes the surgical treatment of a large subcutaneous tumour in a Quarter Horse colt. The histopathological appearance of the mass was most consistent with a haemangioma. While these neoplasms of vascular origin are often difficult to characterise, it has been suggested that there is a continuum of types with some cases falling between the categories. Further classification of vascular tumours requires special stains and immunohistochemical techniques.